Kajian Psikoanalisis Freud terhadap Degradasi Moral dan Kekerasan Seksual - Muhammad Ihwan Safrudin; Disyela Apriswa Mandai; Dadan Firdaus (Indo Publishing, 2026)
The rapid development of information technology and globalization has led to the moral degradation of university students, including the emergence of cases of sexual violence on the campus. This research is intended to analyze the psychological dynamics of sexual violence as the form of moral degradation in the perspective of Sigmund Freud’s Psychoanalysis theory namely the structure of personality Id, Ego, and Superego and also analyze the internalization of akhlak values through the Sufi concept of tazkiyatun nafs as the prevention of the degradation. This study uses a qualitative library research method with content analysis technique . The case of sexual violence at the Faculty of Law, Universitas Indonesia (FH UI) is used as a case illustration. The results show that sexual violence behavior is based on the dominance of the Id and the weakening of the Superego with the failure of the Ego to perform sublimation as a compound. The internalization of akhlak values and the practice of tazkiyatun nafs are proposed as holistic spiritual solutions to strengthen the Ego and regain the moral integrity.